(untitled) (Mustansiria Dental Journal, 2005)
The major goal of periodontal therapy is to eliminate the periodontal pockets and ` to create a connective tissue attachment. Forty two patients with periodontal pockets subdivided into 2 groups, Tissucol group, 21 patient were treated surgically with introduction of` Tissucol bioadhesive material, other 21 patients were also treated surgically their flaps were sutured according to the traditional suture technique. The result showed that there were a significant gain in the pocket depths reduction and attachment levels in both groups, but that of Tissucol group is superior than that of suturing group. The patients were followed for six months, the stability of the gain in Tissucol group still significant, while that of suturing group showed a significant loss in pocket depth reduction and attachment level during the six months of follow up. The result suggested that the tissucol help in creation of connective tissue attachment and preventing the invasion of epithelial growth. The role of oral hygiene were also taken in consideration , as long the oral hygiene kept in healthy state level as the gain in pocket depth and attachment level maintained stable .